Preparation, characterization, in-vivo evaluation and application of nanoliposomal polyunsaturated for food enrichment - Rasti, Babak (2013)
The 0)-3 fatty acids, Eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), have low water-solubility and are very sensitive to oxidation; therefore there is a need for new methods to solubilize and protect such sensitive compounds. One approach for increasing the level of 00-3 in our diet is to increase the 00-3 content of food formulations with micro- and nano-encapsulated 0)-3. The aim of the present research was to develop, optimize and characterize the formation of stable liposomal nanocomplexes for encapsulation and delivery of 0)-3 FAs with high in-vivo bioavailability and suitability for food enrichment. Liposomes were prepared by Bangham/conventional thin-layer evaporation as reference method and Mozafari method (direct hydration without using organic solvents). In the first study, the application of the response surface methodology (RSM) to develop an optimal preparation condition namely shear rate (600-1000 rpm), mixing time (30-60 min) and sonication time (10-20 min) for DHA and EPA nanoliposomes was studied. Fifteen lipid mixtures were generated by the Box-Behnken design and nanoliposomes were prepared by the Mozafari method. Nanoliposomes were characterized with respect to encapsulation/entrapment efficiency (EE) and particle size (PS). The results were then applied to estimate the coefficients of response surface model and to determine the optimal preparation conditions with maximum EE and minimum PS. The response surface analysis showed no significant (p > 0.05) lack of fit for the reduced models. The response optimization of experiments was the shear rate: 795 rpm; mixing time: 60 min; and sonication time: 10 min with the average diameter of 81.4 nm and EE of 100%. In the second study, using the optimum preparation conditions from the first study, the influence of liposome composition namely phospholipid (PL; 2-8 g), DHA and EPA (300-600 mg) and glycerol (1-3% w/w) on EE and PS was evaluated and optimized by RSM. The response optimizations of experiments were the PL: 6.87 g and 0)-3: 300 mg. The optimal nanoliposome had an average diameter of72.9 nm and EE of 100 %. In the third study, the physical and relative oxidative stability of freshly prepared and stored liposomal and nanoliposomal systems of DHA and EPA were investigated. The effects of organic solvents on the oxidative stability of liposomal 00-3 produced by both methods were compared. The highest physicochemical stability was observed in PUFA liposomes prepared by the Mozafari method, followed by conventional liposomes and bulk PUFAs. There was no significant (p > 0.05) change in physicochemical stability of nanoliposomal 00-3 during 10 months of cold storage (4°C). Moreover, the comparison between liposomes (>200 nm) and nanoliposomes (50-200 nm) revealed that the surface charge, physical stability and oxidative stability of liposomal PUFAs increased as the size of the liposomes decreased. In-vivo experiment was carried out, the fourth study, to determine whether EPA and DHA, esterified in triglycerides as oil or in PL as liposome and nanoliposome, exhibit comparable fates in plasma and liver lipids. PL and TO mixtures with close contents of EPA and DHA were administered to 80 male Sprague-Dawley rats for 8 weeks. Most relevant events occurred after 8 weeks for all treatments. However, significant (p < 0.05) increase in 00-3 content of plasma and liver was observed from the second week of the experiment. At that time, nanoliposomes and liposomes caused higher increase in the DHA and EPA contents of plasma and liver compared with oil. Liposome and fish oil feedings caused a marked increase in the amounts of 00-3 PUFA. However, nanoliposomes increased the 00-3 level in significantly (p < 0.05) higher amount compared with liposomes and oil. Finally, application of nanoliposomal 00-3 in bread and milk was compared with unencapsulated and microencapsulated 00-3. Objective discrimination sensory test was conducted to determine the perceptible sensory difference or similarity between unencapsulated (fish oil), microencapsulated and nanoliposomal 00-3 enriched food. Results of the sensory evaluation showed no significant detectable difference (p > 0.05) between the control and nanoliposomal 00-3 enriched samples. In contrast, samples enriched with fish oil or microencapsulated 00-3 showed significant (p < 0.05) detectable fishy flavor. Moreover, significantly (p < 0.05) higher 00-3 % recovery and lower peroxide and anisidine values were observed in nanoliposomal 00-3 enriched samples in comparison with other samples. In conclusion, we have successfully developed a safe, effective and reproducible method for protection, delivery and application of 00-3 FAs in food system. However, the safety of the nanoliposomes after ingestion in humans should be evaluated.